Pengaruh Disiplin Kerja, Kerjasama Tim dan Kompensasi terhadap Kinerja Karyawan Generasi Milenial di Perusahaan Manufaktur Plastik - Maulana, Rega; Yusuf, M. Ali (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to examine the influence of work discipline, teamwork and compensation on employee performance in manufacturing companies. The research method used is descriptive using a questionnaire as a data collection instrument. For data analysis using classical assumption tests, multiple regression analysis and hypothesis testing. The research findings indicate that work discipline (X1), teamwork (X2), and compensation (X3) have a positive and significant impact on employee performance when considered simultaneously. This suggests that improving these three factors together can substantially enhance overall employee performance. Additionally, the study reveals that each factor—work discipline, teamwork, and compensation individually contributes a significant positive effect on employee performance. This highlights the importance of focusing on each of these areas to achieve optimal performance from employees.